2009
DOI: 10.1158/0008-5472.can-08-4102
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophosphamide Augments Antitumor Immunity: Studies in an Autochthonous Prostate Cancer Model

Abstract: To study the immune response to prostate cancer, we developed an autochthonous animal model based on the transgenic adenocarcinoma of the mouse prostate (TRAMP) mouse in which spontaneously developing tumors express influenza hemagglutinin as a unique, tumor-associated antigen. Our prior studies in these animals showed immunologic tolerance to hemagglutinin, mirroring the clinical situation in patients with cancer who are generally nonresponsive to their disease. We used this physiologically relevant animal mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
126
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(134 citation statements)
references
References 47 publications
8
126
0
Order By: Relevance
“…A commonly used chemotherapeutic agent CY can selectively deplete Treg cells when administered more frequenty or "metronomically" at a dose substantially lower than the maximum tolerated dose. Such low-dose CY is not only immunostimulatory but also avoids CY high-dose toxicity (16,42). In addition, the restoration of Treg numbers and function 10 days after low-dose CY administration implies that a limited period of Treg cell inhibition may avoid potential autoimmunity (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A commonly used chemotherapeutic agent CY can selectively deplete Treg cells when administered more frequenty or "metronomically" at a dose substantially lower than the maximum tolerated dose. Such low-dose CY is not only immunostimulatory but also avoids CY high-dose toxicity (16,42). In addition, the restoration of Treg numbers and function 10 days after low-dose CY administration implies that a limited period of Treg cell inhibition may avoid potential autoimmunity (15).…”
Section: Discussionmentioning
confidence: 99%
“…It is now clear that low-dose CY can selectively ablate CD4 + CD25 + Treg cells, leading to the enhancement of immune responses (14,15). Based on this principle, low-dose CY has been successfully tested in the treatment of various types of tumor (16)(17)(18). Moreover, our observations indicated that low-dose CY can effectively prevent the recurrence of condylomata acuminata caused by human papillomavirus (HPV) by selectively depleting Treg cells.…”
Section: Cd4mentioning
confidence: 96%
“…Interestingly, several chemotherapeutic drugs have the potential to mitigate immunosuppression by Treg cells and MDSCs. Many studies have shown that low-dose CTX increases anti-tumor immune responses in tumor-bearing hosts by mitigating Treg cell-mediated immunosuppression [11][12][13][14][15][16]. CTX has multifaceted effects on immunity.…”
Section: Immunologicalmentioning
confidence: 99%
“…The alkylating agent CYP, when given in low doses, selectively induces T reg cell depletion (Berd & Mastrangelo, 1987;Greten et al, 2010). Since the immunomodulatory properties of CYP include also DC activation and polarization of immune response to T-helper (T H )-1 cytokine secretion, the drug has been used in combination with both tumorcell vaccines and, more recently, with DC vaccines (Radojcic et al, 2010;Tzai et al, 1996;Wada et al 2009;Wersäll & Mellstedt, 1995). However, the efficacy of CYP in improving the effects of DC vaccines is still an open issue.…”
Section: T-regulatory (T Reg ) Cellsmentioning
confidence: 99%